USING STUDENT TEAM ACHIEVEMENT DIVISION (STAD) METHOD TO IMPROVE THE WRITING ABILITY OF THE SECOND YEAR STUDENTS OF MTs BUSTANUL ULUM PEKANBARU - Widya Asri Wandari Asri Wandari; Rumiri Aruan Rumiri Aruan; Desri Maria Sumbayak Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: After doing a small observation in the process of teaching and learning English and having an interview with one of English teachers in MTs Bustanul Ulum Pekanbaru especially in the second year students. Most of the students were lack of interest to learn writing ability and their writing score were lower than KKM so the teacher and the researcher needed to find out the way to attract the students’ interest in learning writing ability. Students Teams Achievement Divisions (STAD)method was chosen to improve the students’ writing ability in writing recount text because STAD method could attract the students’ interest by giving a reward to the students in the end of meeting. Then, the researcher also want to introduce about cooperative learning method to the students through STAD method. This research was aimed to find out whether STAD method could improve the students’ writing ability. The participants were 31 students of second year students. All of the students were girls. The data were collected from August 21 until Sept 25, 2015. This research was an Classroom Action Research (CAR) which consisted of three cycles, two meetings in each cycle. The research finding showed that STAD method could improve the students’ writing ability, the improvement could be seen from pre-test with average score was only 44,3 (Moderate) and post test-three increased to 70,6 (Good). STAD method was attracted and motivated the students in learning writing. It also helped the students to build their confidence and became more active in achieving their objectives. STAD methode could improve the students’ writing ability in writing recount text.Keywords: Students Teams Achievement Divisio (STAD), students’ writing ability, recount text